The chain reaction : pioneers of nuclear science - Fox, Karen (New York : Franklin Watts, 1998)
Profiles seven people--including Marie Curie, Enrico Fermi, Robert Oppenheimer, and Andrei Sakharov--whose study of the atom has shaped the field of nuclear science during the twentieth century.
Includes bibliographical references (p. 133-135) and index.
Booklist.
L.A. Recommended Foreign Language.
School Library Journal.
Young Adult
Keywords: Nuclear physicists -- Biography -- Juvenile literature; Nuclear physics -- History -- Juvenile literature; Nuclear physicists; Nuclear physics; Nuclear physicists -- Biography; Nuclear physics -- History